Investigation of Risperidone Treatment Associated With Enhanced Brain Activity in Patients Who Stutter - Maguire, Gerald A.; Yoo, Bo Ram; SheikhBahaei, Shahriar (Frontiers in Neuroscience, 2021)
Stuttering is a childhood onset fluency disorder that leads to impairment in speech. A randomized, double-blinded placebo-controlled study was conducted with 10 adult subjects to observe the effects of risperidone (a dopamine receptor 2/serotonin receptor 2 antagonist) on brain metabolism, using [18F] deoxyglucose as the marker. At baseline and after 6 weeks of taking risperidone (0.5–2.0 mg/day) or a placebo pill, participants were assigned to a solo reading aloud task for 30 min and subsequently underwent a 90-min positron emission tomography scan. Paired t-tests were performed to compare the pre-treatment vs. post-treatment in groups. After imaging and analysis, the blind was broken, which revealed an equal number of subjects of those on risperidone and those on placebo. There were no significant differences in the baseline scans taken before medication randomization. However, scans taken after active treatment demonstrated higher glucose uptake in the specific regions of the brain for those in the risperidone treatment group (p < 0.05). Risperidone treatment was associated with increased metabolism in the left striatum, which consists of the caudate and putamen, and the Broca’s area. The current study strengthens previous research that suggests the role of elevated dopamine activity and striatal hypometabolism in stuttering. We propose that the mechanism of risperidone’s action in stuttering, in part, involves increased metabolism of striatal astrocytes. We conclude that using neuroimaging techniques to visualize changes in the brain of those who stutter can provide valuable insights into the pathophysiology of the disorder and guide the development of future interventions.